Alginic acid, a functional dietary ingredient derived from Ecklonia maxima stipe, attenuates the pro-inflammatory responses on particulate matter-induced lung macrophages - D.P. Nagahawatta; Hyo-Geun Lee; N.M. Liyanage; H.H.A.C.K. Jayawardhana; Lei Wang; Hyun-Soo Kim; You-Jin Jeon (Journal of Functional Foods, 2023)
Alginate is a prominent food component extensively employed in developing functional food items and a dietary supplement with significant anti-inflammatory potential. Globally, rising air pollution by particulate matter (PM) has become a significant threat to humans, causing collateral lung tissue damage by inflammation. Therefore, the present study aimed to evaluate the anti-inflammatory potential of alginate isolated from Ecklonia maxima stipes (EMSA) against lung inflammation due to PM exposure. Initial results from cell viability, nitric oxide, prostaglandin E-2, and pro-inflammatory cytokine production assays showed that EMSA has potential anti-inflammatory activity against PM-induced inflammation. Western blot and qPCR results revealed the anti-inflammatory potential of EMSA through inflammatory signaling pathways, further confirmed by in vivo results and inductively coupled plasma-optical emission spectrometry. Therefore, EMSA can produce low-cost and high-quality alginate for several fields, such as functional foods using E. maxima stipes, a natural source such as functional foods, pharmaceuticals, and nutraceuticals.